Synthesis, crystal structures and insulin-like activity of two new oxidovanadium(V) complexes with aroylhydrazones and maltol mixed-ligands. (24th November 2017) - Chen, Xiang-Fei; Wang, Tian-Rui; Ma, Zheng; Yu, Yan; Ling Tang,; Jin, Li-Yuan; Sheng, Gui-Hua; Zhu, Hai-Liang
Graphical abstract: Two new oxidovanadium(V) complexes with formula [VOLL′], (L = L 1  = 2-ethyl-3-hydroxy-4H-pyran-4-one for1, L = L 2  = 2-methyl-3-hydroxy-4H-pyran-4-one for2, and L′ = (E)-N′-(2-hydroxy-3-methoxybenzylidene)pivalohydrazide) have been prepared. The complexes have been characterized by single crystal X-ray determination. The V atom in each complex is coordinated by the NOO donor atoms of L′ and the OO donor atoms of L, and one oxido group, forming octahedral coordination. The complexes were administered intragastrically to both normal and STZ-diabetic mices for two weeks. The biological activity results show that the complexes at doses of 10.0 and 5.0 mg V·kg −1, can significantly decrease the blood glucose level in STZ-diabetic mices, but the blood glucose level in the treated normal mices was not altered. Abstract: Two new oxidovanadium(V) complexes with formula [VOLL′], (L = L 1  = 2-ethyl-3-hydroxy-4H-pyran-4-one for1, L = L 2  = 2-methyl-3-hydroxy-4H-pyran-4-one for2, and L′ = (E)-N′-(2-hydroxy-3-methoxybenzylidene)pivalohydrazide) have been prepared. The complexes have been characterized by single crystal X-ray determination. The V atom in each complex is coordinated by the NOO donor atoms of L′ and the OO donor atoms of L, and one oxido group, forming octahedral coordination. The complexes were administered intragastrically to both normal and STZ-diabetic mices for two weeks. The biological activity results show that the complexes at doses of 10.0 and 5.0 mg V·kg −1, can significantly decrease the blood glucose level in STZ-diabetic mices, but the blood glucose level in the treated normal mices was not altered.